Determinants of the Financial Capability: The Mediating role of Financial Self-efficacy and Financial Inclusion - Al Rahahleh, Naseem (International Journal of Economics and Financial Issues, 2023)
Identifying and addressing the predictors of financial capability in the context of a developing country such as Kingdom of Saudi Arabia is vital to advancing the financial behavior literature. Financial self-efficacy initially develops from financial literacy and the continuing development of each depends on the continuing development of the other. However, the exact nature of the relationship between financial self-efficacy and the relationship between financial literacy and financial inclusion remains a subject for argument. We, therefore, propose a model comprising both direct and indirect mechanisms with the goal of moving towards a logically complete understanding of how to determine financial capability. Our findings support all the proposed roles such that achieving financial literacy through its components constitutes the vital first step to gaining subsequent financial capability determinants. Further, our findings point to the need for a widespread and concerted effort to improve financial awareness among Saudi citizens. Given that our findings arise from a broad-based investigation into how financial capability is determined, they can be used as a basis for modifying existing approaches and for developing new directions to providing financial education to the citizenry.